How do the Characteristics of Gold Mining Projects Affect the Level of Resistance among Local Communities? A Comparative Study - Şükrü Özen; Hayriye Özen (İstanbul Üniversitesi Sosyoloji Dergisi)
In this study, we aim to understand how the factors associated with gold mining projects affect the level of resistance of local communities against gold mining. Unlike previous research that claimed that the objectively observable features of mining projects directly affect the level of resistance, we argue from a post-structuralist perspective that objective features can affect resistance only as they are articulated in anti-mining and pro-mining discourses. Based on this premise, we compare the features of the Artvin-Cerrattepe, Eşme-Kışladağ, Menderes-Efemçukuru and İliç-Çöpler projects between 1994 and 2010 by associating them with anti-mining and pro-mining discourses as well as resistance levels. Our comparison shows that the features of projects, such as the mining company’s country of origin, the use of cyanide, the value of the mine for the company, the proximity of the mining site to settlement areas, its topographic location, and the income level of locals that the mining site directly impacts, affect the level of resistance only through the meanings that they take in the anti-mining and pro-mining discourses. Our study also reveals that the resistance level is unrelated to the kind of mineral, mining quarry, or grade. Our study contributes to the relevant literature by offering both a theoretical framework that relates the characteristics of mining projects to the level of local resistance in a novel way, as well as three influential project characteristics neglected in the literature – the mining company’s country of origin, the value of the mine for the company, and the mining site’s topographic location.